(untitled) (Research, Society and Development, 2022)
Objectives: To evaluate the curricular component aimed at teaching the Brazilian Sign Language (Libras) in Dentistry courses at public higher education institutions in Brazil. Methods: This is an observational, cross-sectional, documentary research with a quantitative approach, where data collection was performed through a form, filled in according to information present in the pedagogical plan of each institution. The search for the data was through the Ministry of Education’s electronic address, including all Dentistry courses from public institutions in Brazil. The form was filled in with information about the presence of the discipline, whether optional or mandatory, nomenclature, workload, semester in which it is offered, disciplinary integration and whether the discipline was theoretical or practical. Results: After data collection, it was observed that public institutions in the Midwest, Northeast and South regions were those in which the Libras discipline was more prevalent, with 100%, 89.5% and 75% respectively. In relation to public higher education institutions in the North and Southeast, only 50% and 42.1%, respectively, offered this education. Most Libras disciplines, when present, were strictly theoretical. Regarding the other characteristics analyzed (nomenclature, number of hours, optional or mandatory, semester in which it is offered) it was possible to observe a variation by institution. Conclusion: It was possible to conclude a specificity in the offer of the discipline according to the pedagogical plan of each course and a difference between the regions of the country.